(l)-Prolinamide imidazolium hexafluorophosphate ionic liquid as an efficient reusable organocatalyst for direct asymmetric aldol reaction in solvent-free condition. Issue 102 (21st October 2016) - Yadav, Geeta Devi; Singh, Surendra
Abstract : We have designed a new hydrophobic ionic liquid derived from bromoester of trans -4-hydroxy-(l )-prolinamide and N -methylimidazole. Abstract : We have designed a new hydrophobic ionic liquid derived from bromoester of trans -4-hydroxy-(l )-prolinamide and N -methylimidazole. (l )-Prolinamide imidazolium hexafluorophosphate ionic liquid (2 mol%) found to be an excellent organocatalyst for direct asymmetric aldol reaction between 4-nitrobenzaldehyde and cyclohexanone using acetic acid (2 mol%) as an additive at −15 °C in solvent-free condition, the aldol product was afforded in excellent yield with diastereomeric ratio ( anti / syn ; 97 : 3) and 94% ee of anti -aldol product. Ionic liquids can catalyze the direct aldol reaction between benzaldehyde derivatives and cycloalkanones and the best dr ( anti / syn ; 99.9/0.01) and 99% ee was obtained for aldol product of 2-trifluoromethyl benzaldehyde and cyclohexanone. (l )-Prolinamide imidazolium hexafluorophosphate ionic liquid was reused up to 6 continuous cycles without decrease in the conversion of the product with 92% ee and found to be superior than its counterpart trans -4-hydroxy-(l )-prolinamide. Continuous cycle experiments do not require isolation of the catalyst after each cycle. The results of reusability of the ionic liquid catalyst were found to be better than most of other reported reusable catalysts.